دراسة الخصائص المورفولوجية لأشجار النخيل المذكرة والمؤنثة بمنطقة وادي سوف الجزائر - باي, هناء; ونيسي, تبر (Université of Eloued, 2018)
The aim of this study is to investigate the concept of the cultivar in the male date trees and their compatibility with the female date trees in Reguiba region based on the farmers of the region and the morphological study by identifying the common characteristics between the male and female date trees, by measuring the morphological parameters of the leaf and reproductive organs at the male and female date trees on three cultivars (Deglet Nour – Degla Beida – Ghars) during the season of 2017-2018. The obtained results showed that there was a great diversity between the studied cultivars and a significant compatibility between the male and female date trees for each studied cultivar. However the leaf properties results showed compatibility between the studied female date trees cultivars and the male date trees in the following characteristics: paper length - maximum width of paper - number of thorns - length of the area free from thorns. The results of the study on the reproductive organs showed the compatibility of each cultivar between the male and female date trees in the following characteristics: the number of pollen - the length of the pollen - the width of the pollen - the number of the Shamrock - the length of the Shamrock - the number of flowers per Shamrock, the results of the hierarchical clustering (classification Ascendant Hierarchique (CAH)) demonstrated that there are common characteristics between each cultivar and its male and female date trees. These results describe the validity to applicate the concept of the cultivar on the male date trees.
Biologie et Valorisation des Plantes
Keywords: أشجار النخيل; Phoenix dacfylifera L